Preparation method of electromagnetic shielding film and electromagnetic shielding film

By using collagen fibers and polyvinyl alcohol as film forming agents in electromagnetic shielding films, combined with MXene and liquid metal as fillers, the problem of insufficient thermal conductivity and electrical conductivity of traditional electromagnetic shielding films is solved through hot pressing, and the problem of insufficient thermal conductivity and electrical conductivity of traditional electromagnetic shielding films is achieved. Good electromagnetic shielding effect and thermal management.

CN119391030APending Publication Date: 2025-02-07SHENZHEN SUNWAY COMM
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411532271.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The thermal conductivity and electrical conductivity of traditional electromagnetic shielding films are poor, making it difficult to effectively solve the problems of electromagnetic interference and heat accumulation.

Method used

Collagen fiber powder and polyvinyl alcohol are used as film forming agents, combined with MXene powder and liquid metal as fillers, and electromagnetic shielding films are prepared by hot pressing treatment.

Benefits of technology

The conductivity and thermal conductivity of the electromagnetic shielding film are improved, the electromagnetic shielding effect is enhanced, the heat accumulation problem is effectively solved, and the flexibility and wear resistance of the film are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391030A_ABST
    Figure CN119391030A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides a preparation method of an electromagnetic shielding film and the electromagnetic shielding film. The collagenous fiber powder and the polyvinyl alcohol are used as film-forming agents, so that the prepared electromagnetic shielding film is good in flexibility, tensile strength and wear resistance. The MXene powder and the liquid metal are used as fillers, and the MXene has good conductivity and can effectively interact with electromagnetic waves to convert electromagnetic energy into heat energy or energy in other forms so as to realize absorption and scattering of the electromagnetic waves. The liquid metal has relatively high electric conductivity and thermal conductivity, and when the liquid metal is compounded with MXene, the liquid metal can be filled in interlayers or pores of the MXene, so that the compactness and uniformity of the electromagnetic shielding film are improved, and a continuous conductive network is formed. According to the electromagnetic shielding film, the overall conductivity and heat dissipation performance of the electromagnetic shielding film are improved, the problem of heat accumulation is effectively solved, the contact area and interaction between electromagnetic waves and the electromagnetic shielding film are increased, and the electromagnetic shielding effect is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of electromagnetic shielding films, and in particular to a method for preparing an electromagnetic shielding film and the electromagnetic shielding film. Background Art

[0002] With the rapid popularization of the fifth generation of mobile communication technology (5G), electronic devices are becoming increasingly miniaturized and flexible. The increase in power density due to high integration has aggravated the problems of electromagnetic interference and heat accumulation, seriously affecting the life and safety of electronic devices. Therefore, the development of electromagnetic shielding films with high electrical and thermal conductivity is crucial to solve electromagnetic interference and heat accumulation.

[0003] Electromagnetic shielding films can be prepared by mixing solid fillers and polymer matrices, but traditional solid fillers are difficult to establish continuous conductive channels in the polymer matrix, resulting in poor thermal conductivity and electrical conductivity of the prepared electromagnetic shielding films. Summary of the invention

[0004] The present application provides a method for preparing an electromagnetic shielding film and the electromagnetic shielding film, aiming to improve the problem of poor thermal conductivity and electrical conductivity of the electromagnetic shielding film.

[0005] In the first aspect, an embodiment of the present application provides a method for preparing an electromagnetic shielding film, comprising: mixing collagen fiber powder with polyvinyl alcohol to obtain a first mixture, dissolving the first mixture in a first solvent to obtain a first mixed liquid. MXene powder is dissolved in a second solvent to obtain a MXene solution. The first mixed liquid is mixed with the MXene solution for a first time to obtain a second mixed liquid. Liquid metal is provided, and the liquid metal is added to the second mixed liquid to dissolve to obtain a third mixed liquid. The third mixed liquid is coated on a first substrate and allowed to stand for a second time to obtain a first gel. The first gel is subjected to hot pressing to obtain an electromagnetic shielding film.

[0006] In some embodiments, the collagen fiber powder is mixed with polyvinyl alcohol and then dissolved in a first solvent to obtain a first mixed liquid, which includes: mixing 8g to 12g of the collagen fiber powder with 3g to 8g of the polyvinyl alcohol, dissolving in 60ml to 100ml of the first solvent, stirring and heating to 70°C to 100°C to obtain the first mixed liquid.

[0007] In some embodiments, dissolving the MXene powder in the second solvent to obtain the MXene solution comprises: dissolving 5 g to 10 g of the MXene powder in 85 ml to 100 ml of the second solvent, stirring and heating to 70° C. to 100° C. to obtain the MXene solution.

[0008] In some embodiments, the hot pressing of the first gel to obtain the electromagnetic shielding film includes: placing the first gel in a hot press at a temperature of 60°C to 100°C and a pressure of 30MPa to 50MPa for 5min to 10min to obtain the electromagnetic shielding film.

[0009] In some embodiments, the weight ratio of the first mixture to the MXene powder is (2-4): 1. The weight ratio of the liquid metal to the first mixture is 1: (3-5).

[0010] In some embodiments, the collagen fiber powder includes at least one of biomass collagen fibers, recombinant collagen fibers, and synthetic collagen fibers.

[0011] In some embodiments, the first solvent includes at least one of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, acetonitrile, hexamethylphosphoric triamide, and propylene carbonate. The second solvent includes at least one of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, acetonitrile, hexamethylphosphoric triamide, and propylene carbonate.

[0012] In some embodiments, the liquid metal includes at least one of mercury, gallium, cesium, sodium potassium alloy, gallium indium alloy, and gallium indium tin alloy.

[0013] In some embodiments, the first substrate includes any one of a PET substrate, a PC substrate, a PBT substrate, a PLA substrate, a PEN substrate, and a PE substrate.

[0014] In a second aspect, an embodiment of the present application provides an electromagnetic shielding film, which is prepared by the preparation method as described in any one of the first aspects.

[0015] Different from the related art, the embodiment of the present application provides a method for preparing an electromagnetic shielding film. Collagen fiber powder and polyvinyl alcohol are used as film-forming agents to make the prepared electromagnetic shielding film have good flexibility, tensile strength and wear resistance. MXene powder and liquid metal are used as fillers. MXene has good electrical conductivity. MXene can effectively interact with electromagnetic waves and convert electromagnetic energy into heat energy or other forms of energy, thereby realizing the absorption and scattering of electromagnetic waves. Liquid metal has high electrical conductivity and thermal conductivity. When liquid metal is compounded with MXene, the layered structure of MXene provides support and confined space for liquid metal, reducing the agglomeration and loss of liquid metal. Liquid metal can be filled in the interlayer or pores of MXene to improve the density and uniformity of the electromagnetic shielding film to form a continuous conductive network. Not only does it improve the overall conductivity and heat dissipation of the electromagnetic shielding film, effectively solving the problem of heat accumulation, but it also increases the contact area and interaction between electromagnetic waves and the electromagnetic shielding film, promoting the enhancement of the electromagnetic shielding effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] One or more embodiments are exemplarily described by corresponding drawings, which do not constitute limitations on the embodiments. Elements with the same reference numerals in the drawings represent similar elements, and the figures in the drawings do not constitute proportional limitations unless otherwise stated.

[0017] Figure 1 It is a flow chart of some methods for preparing electromagnetic shielding films provided in the embodiments of the present application. DETAILED DESCRIPTION

[0018] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0019] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "several" and "multiple" is more than two, unless otherwise clearly and specifically defined.

[0020] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0021] Reference to "embodiment" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. In addition, the technical features involved in the different embodiments of the present application described below may be combined with each other as long as they do not conflict with each other.

[0022] In the first aspect, the present application embodiment provides a method for preparing an electromagnetic shielding film, please refer to Figure 1 , Figure 1 The flowchart of the preparation method of some electromagnetic shielding films provided in the embodiments of the present application. The preparation method comprises the following steps:

[0023] Step S1: Collagen fiber powder is mixed with polyvinyl alcohol to obtain a first mixture, and the first mixture is dissolved in a first solvent to obtain a first mixed solution.

[0024] Collagen fiber is one of the main components of the extracellular matrix and has good biocompatibility. Its molecular structure contains a large number of amino acid residues such as glycine, proline and hydroxyproline. The peptide bonds formed between these amino acids give collagen fibers a certain strength and good flexibility, which can add biological activity and certain mechanical properties to electromagnetic shielding films.

[0025] Polyvinyl alcohol (PVA) is a water-soluble polymer with good film-forming properties, adhesion and chemical stability. Its molecular chain contains a large number of hydroxyl groups, which can form hydrogen bonds with water molecules, making polyvinyl alcohol have good water solubility. In addition, the molecular chain structure of polyvinyl alcohol can provide certain flexibility and tensile strength for electromagnetic shielding films.

[0026] Collagen fiber powder and polyvinyl alcohol are used as film-forming agents to make the prepared film have good flexibility, and the film has good tensile strength and wear resistance.

[0027] The first solvent needs to satisfy the requirement of being able to dissolve collagen fiber powder and polyvinyl alcohol at the same time. For example, the first solvent includes at least one of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, acetonitrile, hexamethylphosphoric acid triamide, and propylene carbonate. The preferred first solvent may be dimethyl sulfoxide (DMSO) or N,N-dimethylformamide (DMF). Dimethyl sulfoxide is a polar organic solvent having the characteristics of high boiling point, high polarity, and high dielectric constant. Dimethyl sulfoxide has good solubility for collagen fibers and polyvinyl alcohol. Dimethyl sulfoxide can interact with polar groups in collagen fiber powder and polyvinyl alcohol molecules. For collagen fibers, dimethyl sulfoxide can form hydrogen bonds or other intermolecular forces with polar groups on amino acid residues in collagen fibers, such as hydroxyl groups, amino groups, etc., so that the collagen fiber powder gradually dissolves. For polyvinyl alcohol, dimethyl sulfoxide can interact with hydroxyl groups on polyvinyl alcohol molecular chains, destroy hydrogen bonds between polyvinyl alcohol molecules, and promote the dissolution of polyvinyl alcohol.

[0028] The first mixed solution obtained by mixing the collagen fiber powder with polyvinyl alcohol has good film-forming properties.

[0029] In some embodiments, the collagen fiber powder includes at least one of biomass collagen fiber, recombinant collagen fiber, and synthetic collagen fiber. Preferably, the collagen fiber powder includes biomass collagen fiber, which is derived from natural animal tissues, such as collagen fiber extracted from animal skins such as pigskin and cowhide, and has the advantages of a wide source of raw materials and relatively low cost. In addition, biomass collagen fiber is easily degraded by microorganisms, and the degraded product is pollution-free and has no toxic side effects.

[0030] In some embodiments, the collagen fiber powder is mixed with polyvinyl alcohol and then dissolved in a first solvent to obtain a first mixed liquid, comprising mixing 8g to 12g of the collagen fiber powder with 3g to 8g of the polyvinyl alcohol, dissolving the mixture in 60ml to 100ml of the first solvent, stirring and heating to 70°C to 100°C to obtain the first mixed liquid.

[0031] Step S2: MXene powder is dissolved in a second solvent to obtain a MXene solution.

[0032] MXene is a new type of transition metal carbide or carbonitride with a two-dimensional nanosheet structure. It is generally prepared by selectively removing the A atomic layer in the MAX phase through chemical etching and other methods. The general chemical formula of MXene can be expressed as M n+1 X n T x(Where M is an early transition metal element, X represents carbon or nitrogen, and T is the active group attached to the surface, such as -OH, -F, -O, etc.). Compared with graphene-based materials, MXene not only has the characteristics of high specific surface area, high conductivity, and good mechanical properties, but also its interlayer spacing and composition are adjustable and controllable. The abundant functional groups such as -OH and -O on the surface give MXene better reactivity and hydrophilicity, allowing it to be well dispersed in aqueous solution. For example, MXene can be materials such as Ti C Tx, Ti CTx, V CTx or Nb CTx.

[0033] The second solvent needs to have good solubility for MXene powder, and the second solvent can interact with the functional groups on the surface of MXene, and is usually a polar solvent. For example, the second solvent includes at least one of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, acetonitrile, hexamethylphosphoric triamide, and propylene carbonate.

[0034] MXene solution is easily affected by environmental factors and becomes unstable, such as oxygen, humidity, etc. In order to improve the stability of MXene solution, some antioxidants can be added to the MXene solution or the oxidation reaction can be inhibited by adjusting the pH value of the MXene solution. The antioxidant can be citric acid, ethylenediaminetetraacetic acid, etc.

[0035] In some embodiments, dissolving the MXene powder in the second solvent to obtain the MXene solution comprises dissolving 5 g to 10 g of the MXene powder in 85 ml to 100 ml of the second solvent, stirring and heating to 70° C. to 100° C. to obtain the MXene solution.

[0036] Step S3: The first mixed solution is mixed with the MXene solution for a first time period to obtain a second mixed solution.

[0037] Step S4: providing liquid metal, and adding the liquid metal into the second mixed liquid to dissolve it, thereby obtaining a third mixed liquid.

[0038] Liquid metal is an amorphous, flowable liquid metal. Liquid metal has good fluidity and high electrical and thermal conductivity. For example, liquid metal includes at least one of mercury, gallium, cesium, sodium-potassium alloy, gallium-indium alloy, and gallium-indium-tin alloy.

[0039] When liquid metal is added to the second mixed liquid, the liquid metal atoms or the atoms of each element in its metal alloy will contact or interact with the collagen fibers, polyvinyl alcohol, MXene and other components in the second mixed liquid. For example, when the liquid metal atoms are gallium-based liquid metal alloys, there are functional groups such as -OH on the surface of MXene. Gallium atoms can be combined with the above functional groups through chemical bonding methods such as covalent bonds or metallic bonds, thereby gradually dissolving in the second mixed liquid. In addition, gallium atoms may also interact with polar groups such as aminohydroxyl groups in collagen fiber molecules, prompting gallium atoms to fully dissolve in the second mixed liquid.

[0040] In some embodiments, the weight ratio of the first mixture to the MXene powder is (2-4): 1. The weight ratio of the liquid metal to the first mixture is 1: (3-5).

[0041] Step S5: coating the third mixed solution on the first substrate and leaving it to stand for a second period of time to obtain a first gel.

[0042] The third mixed liquid is coated on the first substrate, for example, by spin coating, scraping coating, spraying and the like. A uniform liquid film is formed on the first substrate by coating the third mixed liquid, which lays the foundation for the subsequent formation of the first gel. The liquid film is placed on the first substrate and needs to be left to stand for a second period of time, wherein the second period of time is 1.5h to 3h. During the standing process, the third mixed liquid will change on the first substrate. First, the solvent in the third mixed liquid evaporates and the components interact with each other, and the liquid film will gradually change from a liquid state to a gel state, thereby obtaining the first gel. If the second period of time is too short, for example 30 minutes, the solvent cannot fully evaporate, and the interaction between the components is not sufficient, resulting in uneven texture and insufficient strength of the formed first gel, which affects the performance of the electromagnetic shielding film. If the second period of time is too long, for example more than 5h, external impurities may be mixed into the third mixed liquid, contaminating the first gel.

[0043] In some embodiments, the first substrate comprises any one of a PET substrate, a PC substrate, a PBT substrate, a PLA substrate, a PEN substrate, and a PE substrate. Preferably, the first substrate is a PET substrate.

[0044] Step S6: performing heat pressing on the first gel to obtain an electromagnetic shielding film.

[0045] Hot pressing is usually a process of treating the first gel under heating and pressurizing conditions. During the hot pressing process, the high temperature can further fuse and compact the components in the gel, and enhance the chemical or physical bonding between the components. Hot pressing can also make the first gel spread evenly on the first substrate in a hot state, eliminate the pores and bubbles that may exist in the gel, and improve the density and uniformity of the electromagnetic shielding film.

[0046] In some embodiments, the first gel is subjected to heat pressing to obtain an electromagnetic shielding film, comprising placing the first gel in a heat press at a temperature of 60°C to 100°C and a pressure of 30MPa to 50MPa for 5min to 10min to obtain the electromagnetic shielding film.

[0047] When the pressure is 30MPa to 50MPa, the MXene material and liquid metal in the gel will be pressed more tightly, making the conductive path between the electromagnetic shielding films smoother, thereby improving the conductivity, thermal conductivity and electromagnetic shielding properties of the electromagnetic shielding films.

[0048] MXene is a two-dimensional transition metal carbide or carbonitride with good electrical conductivity. Its unique layered structure and rich surface functional groups allow electrons to be easily transmitted inside the electromagnetic shielding film. High conductivity enables MXene to effectively interact with electromagnetic waves, converting electromagnetic energy into heat or other forms of energy, thereby absorbing and scattering electromagnetic waves.

[0049] Liquid metal itself has high electrical conductivity and thermal conductivity. When liquid metal is compounded with MXene, the layered structure of MXene provides support and confined space for liquid metal, reducing the agglomeration and loss of liquid metal. Liquid metal has fluidity and can be filled in the interlayers or pores of MXene, improving the density and uniformity of the electromagnetic shielding film to form a continuous conductive network. It not only improves the overall conductivity and heat dissipation of the electromagnetic shielding film, effectively solving the problem of heat accumulation, but also increases the contact area and interaction between electromagnetic waves and the electromagnetic shielding film, promoting the enhancement of the electromagnetic shielding effect.

[0050] The embodiment of the present application provides a method for preparing an electromagnetic shielding film. Collagen fiber powder and polyvinyl alcohol are used as film-forming agents to make the prepared electromagnetic shielding film have good flexibility, tensile strength and wear resistance. MXene powder and liquid metal are used as fillers. MXene has good electrical conductivity. MXene can effectively interact with electromagnetic waves and convert electromagnetic energy into heat energy or other forms of energy, thereby realizing the absorption and scattering of electromagnetic waves. Liquid metal has high electrical conductivity and thermal conductivity. When liquid metal is compounded with MXene, the layered structure of MXene provides support and confined space for liquid metal, reducing the agglomeration and loss of liquid metal. Liquid metal can be filled in the interlayer or pores of MXene to improve the density and uniformity of the electromagnetic shielding film to form a continuous conductive network. Not only does it improve the overall conductivity and heat dissipation of the electromagnetic shielding film, effectively solving the problem of heat accumulation, but it also increases the contact area and interaction between electromagnetic waves and the electromagnetic shielding film, promoting the enhancement of the electromagnetic shielding effect.

[0051] In a second aspect, an embodiment of the present application provides an electromagnetic shielding film, which is prepared by the preparation method described in any one of the first aspects.

[0052] The preparation method of the electromagnetic shielding film is described below in conjunction with a specific embodiment:

[0053] Example 1

[0054] (1) 10 g of biomass collagen fiber powder was mixed with 5 g of polyvinyl alcohol to obtain a first mixture, the first mixture was dissolved in 85 ml of dimethyl sulfoxide, and the mixture was vigorously stirred in a water bath at 85° C. to obtain a first mixed solution, and the first mixed solution was cooled to room temperature for later use.

[0055] (2) 7.5 g of TiC Tx powder was dispersed in 92.5 ml of dimethyl sulfoxide and stirred vigorously in a water bath at 85°C to obtain a TiC Tx solution.

[0056] (3) 10 ml of the first mixed solution was mixed with 10 ml of the TiC Tx solution at 25° C. for 24 h to obtain a second mixed solution.

[0057] (4) Providing 3 g of liquid metal gallium, adding the liquid metal gallium into the second mixed solution and fully dissolving it to obtain a third mixed solution.

[0058] (5) The third mixed solution is coated on a PET substrate and allowed to stand for 2 hours to obtain a first gel. The first gel is placed on a hot press at a temperature of 70° C. and a pressure of 30 MPa for 5 minutes to obtain an electromagnetic shielding film.

[0059] Example 2

[0060] (1) 10 g of biomass collagen fiber powder was mixed with 5 g of polyvinyl alcohol to obtain a first mixture, the first mixture was dissolved in 85 ml of dimethyl sulfoxide, and the mixture was vigorously stirred in a water bath at 80° C. to obtain a first mixed solution, and the first mixed solution was cooled to room temperature for later use.

[0061] (2) 7.5 g of TiC Tx powder was dispersed in 92.5 ml of dimethyl sulfoxide and stirred vigorously in a water bath at 85°C to obtain a TiC Tx solution.

[0062] (3) 10 ml of the first mixed solution was mixed with 5 ml of the Ti CTx solution at 25° C. for 24 h to obtain a second mixed solution.

[0063] (4) Provide 5 g of gallium-indium alloy, add the gallium-indium alloy into the second mixed solution and fully dissolve it to obtain a third mixed solution.

[0064] (5) The third mixed solution is coated on a PET substrate and allowed to stand for 2 hours to obtain a first gel. The first gel is placed on a hot press at a temperature of 80° C. and a pressure of 45 MPa for 10 minutes to obtain an electromagnetic shielding film.

[0065] Comparative Example 1

[0066] (1) 10 g of biomass collagen fiber powder was mixed with 5 g of polyvinyl alcohol to obtain a first mixture, the first mixture was dissolved in 85 ml of dimethyl sulfoxide, and the mixture was vigorously stirred in a water bath at 80° C. to obtain a first mixed solution, and the first mixed solution was cooled to room temperature for later use.

[0067] (2) 7.5 g of TiC Tx powder was dispersed in 92.5 ml of dimethyl sulfoxide and stirred vigorously in a water bath at 85°C to obtain a TiC Tx solution.

[0068] (3) 10 ml of the first mixed solution was mixed with 5 ml of the Ti CTx solution at 25° C. for 24 h to obtain a second mixed solution.

[0069] (4) The second mixed solution was coated on a PET substrate and allowed to stand for 2 hours to obtain a first gel. The first gel was placed on a hot press at a temperature of 70° C. and a pressure of 30 MPa for 5 minutes to obtain an electromagnetic shielding film.

[0070] Comparative Example 2

[0071] (1) 10 g of biomass collagen fiber powder was mixed with 5 g of polyvinyl alcohol to obtain a first mixture, the first mixture was dissolved in 85 ml of dimethyl sulfoxide, and the mixture was vigorously stirred in a water bath at 80° C. to obtain a first mixed solution, and the first mixed solution was cooled to room temperature for later use.

[0072] (2) 3 g of liquid metal gallium is provided, and the liquid metal gallium is added into the first mixed solution to fully dissolve the liquid, thereby obtaining a second mixed solution.

[0073] (3) The second mixed solution was coated on a PET substrate and allowed to stand for 2 hours to obtain a first gel. The first gel was placed on a hot press at a temperature of 70° C. and a pressure of 30 MPa for 5 minutes to obtain an electromagnetic shielding film.

[0074] The electromagnetic shielding effectiveness and thermal conductivity of the electromagnetic shielding films prepared in Example 1, Example 2, Comparative Example 1 and Comparative Example 2 were tested respectively.

[0075] Electromagnetic shielding effectiveness: Using the waveguide method, the electromagnetic shielding film to be tested is placed in the waveguide, and the shielding effectiveness of the electromagnetic shielding film is calculated by measuring the transmission characteristics of the electromagnetic waves in the waveguide.

[0076] Thermal conductivity: Using the heat flow method, fix the heat source under the electromagnetic shielding film, attach thermistors to the upper and lower surfaces of the electromagnetic shielding film respectively, and calculate the thermal conductivity of the electromagnetic shielding film by measuring the change in resistance.

[0077] The results of electromagnetic shielding effectiveness and thermal conductivity of different embodiments are shown in Table 1.

[0078] Table 1:

[0079] Example Electromagnetic shielding effectiveness (dB) <![CDATA[Thermal conductivity (Wm -1 K -1 )]]> Example 1 75.3 13.52 Example 2 65.4 14.15 Comparative Example 1 55.4 9.64 Comparative Example 2 32.4 11.65

[0080] According to the test results of electromagnetic shielding effectiveness, and by comparing the above-mentioned embodiments and comparative examples, it can be seen that the electromagnetic shielding effectiveness of the electromagnetic shielding films in Examples 1 and 2 is relatively strong, which are 75.3dB and 65.4dB respectively. By comparing Example 1 and Comparative Example 2, no MXene powder is added in Comparative Example 2, so that the electromagnetic shielding effectiveness of the electromagnetic shielding film prepared in Comparative Example 2 is poor, only 32.4dB, which may be because MXene has good conductivity, MXene can effectively interact with electromagnetic waves, convert electromagnetic energy into heat energy or other forms of energy, thereby achieving absorption and scattering of electromagnetic waves, thereby improving the electromagnetic shielding effectiveness of the electromagnetic shielding film. By comparing Example 1, Comparative Example 1 and Comparative Example 2, the electromagnetic shielding effectiveness of the electromagnetic shielding film prepared in Comparative Example 1 is 55.4dB, which may be because when liquid metal is compounded with MXene, the liquid metal can be filled in the interlayer or pores of MXene, improving the density and uniformity of the electromagnetic shielding film, so as to form a continuous conductive network, thereby increasing the contact area and interaction between electromagnetic waves and the electromagnetic shielding film, and promoting the enhancement of the electromagnetic shielding effect.

[0081] According to the test results of thermal conductivity, and by comparing the above embodiments and comparative examples, it can be seen that the thermal conductivity in embodiment 1 and embodiment 2 is relatively high, which is 13.52 Wm -1 K -1 and 14.15Wm -1 K -1 By comparing Example 1 and Comparative Example 1, no liquid metal is added in Comparative Example 1, so that the thermal conductivity of the electromagnetic shielding film prepared in Comparative Example 1 is poor, only 9.64 Wm -1 K -1 This may be because liquid metal has good thermal conductivity. After being compounded with MXene, it can be distributed between MXene layers or in the pores to better dissipate heat and alleviate the problem of heat accumulation.

[0082] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Under the concept of the present application, the technical features in the above embodiments or different embodiments may also be combined, the steps may be implemented in any order, and there are many other changes in different aspects of the present application as described above, which are not provided in detail for the sake of simplicity. Although the present application has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A method for preparing an electromagnetic shielding film, characterized in that: include: Mixing collagen fiber powder with polyvinyl alcohol to obtain a first mixture, and dissolving the first mixture in a first solvent to obtain a first mixed solution; The MXene powder is dissolved in a second solvent to obtain a MXene solution; The first mixed solution is mixed with the MXene solution for a first time to obtain a second mixed solution; Providing liquid metal, and adding the liquid metal into the second mixed liquid to dissolve it, thereby obtaining a third mixed liquid; The third mixed solution is coated on the first substrate and allowed to stand for a second period of time to obtain a first gel; The first gel is subjected to heat pressing treatment to obtain an electromagnetic shielding film.

2. The preparation method according to claim 1, characterized in that: The collagen fiber powder and polyvinyl alcohol are mixed and dissolved in a first solvent to obtain a first mixed solution, comprising: 8 g to 12 g of the collagen fiber powder and 3 g to 8 g of the polyvinyl alcohol are mixed, dissolved in 60 ml to 100 ml of the first solvent, and heated to 70° C. to 100° C. while stirring to obtain the first mixed solution.

3. The preparation method according to claim 1, characterized in that: The step of dissolving the MXene powder in a second solvent to obtain a MXene solution comprises: 5 g to 10 g of the MXene powder is dissolved in 85 ml to 100 ml of the second solvent, and heated to 70° C. to 100° C. while stirring to obtain the MXene solution.

4. The preparation method according to claim 1, characterized in that: The step of subjecting the first gel to a heat pressing process to obtain an electromagnetic shielding film comprises: The first gel is placed in a hot press at a temperature of 60° C. to 100° C. and a pressure of 30 MPa to 50 MPa for 5 to 10 minutes to obtain the electromagnetic shielding film.

5. The preparation method according to claim 1, characterized in that: The weight ratio of the first mixture to the MXene powder is (2-4):1; The weight ratio of the liquid metal to the first mixture is 1:(3-5).

6. The preparation method according to any one of claims 1 to 4, characterized in that: The collagen fiber powder includes at least one of biomass collagen fibers, recombinant collagen fibers, and synthetic collagen fibers.

7. The preparation method according to any one of claims 1 to 4, characterized in that: The first solvent includes at least one of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, acetonitrile, hexamethylphosphoric triamide, and propylene carbonate; The second solvent includes at least one of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, acetonitrile, hexamethylphosphoric triamide, and propylene carbonate.

8. The preparation method according to any one of claims 1 to 4, characterized in that: The liquid metal includes at least one of mercury, gallium, cesium, sodium-potassium alloy, gallium-indium alloy, and gallium-indium-tin alloy.

9. The preparation method according to any one of claims 1 to 4, characterized in that: The first substrate includes any one of a PET substrate, a PC substrate, a PBT substrate, a PLA substrate, a PEN substrate, and a PE substrate.

10. An electromagnetic shielding film, characterized in that: The method is described in any one of claims 1 to 9.